Long-term operation of tunnel-lining ground heat exchangers in tropical zones: Energy, environmental, and economic performance evaluation. (August 2022) - Li, Chenglin; Zhang, Guozhu; Xiao, Suguang; Xie, Yongli; Liu, Xiaohua; Cao, Shiding
Abstract: The application of traditional borehole ground heat exchangers (GHEs) is extremely limited in tropical zones because of the performance degradation induced by thermal imbalances over the years. Unlike traditional borehole GHEs, tunnel-lining GHEs have absorber pipes between the primary and secondary linings, allowing tunnel ventilation to aid in ground temperature recovery during off periods. To date, the application potential of tunnel-lining GHEs in tropical zones has rarely been reported. In this study, a coupled heat transfer model for heat pumps and tunnel-lining GHEs was built to investigate the effects of tunnel ventilation on thermal imbalance and analyze the feasibility of tunnel-lining GHEs in tropical zones under different thermal conductivities of the surrounding rocks, annual average temperatures, and wind velocities. The results showed that tunnel-lining GHEs effectively reduce the influence of thermal imbalance. The maximum outlet temperature increase for absorber pipes induced by thermal imbalance was 0.54 °C for ten years under building cooling, implying that no obvious annual performance degradation of tunnel-lining GHEs occurs in the tropics of China. However, not all tropical zones of China are suitable for tunnel-lining GHEs because of their excessively high outlet temperatures ranging from 31.2 °C to 41.4 °C. Hence, parametric design charts were proposed to determine the outlet temperature for a preliminary evaluation of feasibility. Finally, parametric design charts were employed in an actual tunnel-lining GHEs project in a tropical zone. Energy, environmental, and economic performance were analyzed for this project. The electricity usage and CO2 emission of tunnel-lining GHEs decreased by 24.6% compared to the cooling towers, and the payback period was 5.9 years. Graphical abstract: Image 1